Determination of photon emission probabilities for the main gamma-rays of 223Ra in equilibrium with its progeny. (July 2015) - Pibida, L.; Zimmerman, B.; Fitzgerald, R.; King, L.; Cessna, J.T.; Bergeron, D.E.
Abstract: The currently published 223 Ra gamma-ray emission probabilities display a wide variation in the values depending on the source of the data. The National Institute of Standards and Technology performed activity measurements on a 223 Ra solution that was used to prepare several sources that were used to determine the photon emission probabilities for the main gamma-rays of 223 Ra in equilibrium with its progeny. Several high purity germanium (HPGe) detectors were used to perform the gamma-ray spectrometry measurements. Highlights: Measurements of photon emission probabilities of 223 Ra in equilibrium with its progeny. Use of high purity germanium detectors for gamma-ray spectrometry measurements. Use of the primary activity determination of 223 Ra sources.